Structural pattern of Sub-Himalaya in Dang and Deukhari valleys of western Nepal - Regmi, Amar Deep; Dhital, Megh Raj; Gadtaula, Rishi; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2009)
Detailed geological mapping was carried out in the Siwaliks of western Nepal surrounding the Dang and Deukhari valleys. The investigation of lithostratigraphy and geological structures revealed several thrusts and folds within this Sub-Himalayan belt. The main thrusts are the Bheri Thrust, Babai Backtbrust, Tui Khola Backthrust, and Rapti Backthrust from north to south, respect ively. Similarly, the main folds are the Malai Khola Anticline, Masot Khola Syncline, Satbariya Syncline, Agaiya Syncline, Baijapur Anticline, Bhainsai Khola Anticline, and Khairi Khola Anticline. Also, the study shows that most of the Siwalik rocks are overturned. The geological map of the area illustrates that one of the limbs of most folds bas been truncated by a thrust. This situation clearly demonstrates that the rocks were subjected to intense deformation, and the folds were formed earlier than the thrusts.